2020
DOI: 10.1021/acssuschemeng.0c00263
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Analysis, Economic Optimization, and Environmental Assessment of Hybrid Extractive Distillation–Pervaporation Processes for Dehydration of n-Propanol

Abstract: n-Propanol, as an important chemical raw material, is used as a solvent and intermediate in chemical industrial production and drug synthesis. In chemical production, alcohol and water easily form an azeotrope which is difficult to separate. In this work, a method of dehydration of n-propanol by pervaporation-assisted extractive distillation is proposed. Glycerol is selected as entrainer by quantum chemical calculation. A combined pervaporation unit with cellophane as a membrane is designed to separate the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Many studies have shown that PV modules can efficiently separate MEOH from MEOH/DMC azeotropes, in which hydrophilic membrane materials such as polyvinyl alcohol (PVA) and chitosan are selected to ensure high selectivity for MEOH. In recent years, many studies combining PV and various distillation techniques for efficient separation of liquid mixtures have been reported. However, the process design and simulation of coupling PV and RD for enhancing GC production have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that PV modules can efficiently separate MEOH from MEOH/DMC azeotropes, in which hydrophilic membrane materials such as polyvinyl alcohol (PVA) and chitosan are selected to ensure high selectivity for MEOH. In recent years, many studies combining PV and various distillation techniques for efficient separation of liquid mixtures have been reported. However, the process design and simulation of coupling PV and RD for enhancing GC production have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…As a typical representative of static PI techniques, membrane separation is widely used in the separation of organics and the separation between organics and water. Due to the environmental friendliness and low energy requirements, pervaporation (PV) membrane has become one of the most important membrane separation technologies. In recent years, the PV membrane-distillation hybrid configurations have been widely studied, , which involves RD, extractive distillation, pressure swing distillation, etc. Toth et al , developed a new generation of poly­(vinyl alcohol) membrane PERVAP 1510 for methanol dehydration, which had a higher separation factor and separation index published in the open literature.…”
Section: Introductionmentioning
confidence: 99%
“…Vapor–liquid equilibrium (VLE) data is used as the basic data for designing and optimizing the extractive distillation process. The selection of appropriate solvent is the key to achieve high efficiency and low energy consumption separation . The study of solvent extraction mechanism is of great significance for solvent screening and molecular design.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of appropriate solvent is the key to achieve high efficiency and low energy consumption separation. 7 The study of solvent extraction mechanism is of great significance for solvent screening and molecular design. At present, there are many methods for solvent screening, such as empirical method, group contribution method, 8,9 and computer design method, 10,11 but they cannot explain the extraction mechanism of solvents from a micro perspective view.…”
Section: Introductionmentioning
confidence: 99%